PENGARUH WAHABISME DALAM TAFSIR AYAT-AYAT TAJSIM, TASHBIH DAN TAWASSUL PADA KARYA AL-‘UTHAIMIN - Miatul Qudsia (Institut Agama Islam Negeri (IAIN) Keiri, 2020)
This study aims to analyze the forms of tajsim and tashbih in the interpretation of Sheikh al-’Uthaimin. Although this statement was strongly rejected by Sheikh al-’Uthaimin himself and Muhammad bin ‘Abd al-Wahhab. This analysis is focused on 4 verses, surat al- Rahman verse 27, Hud verse 37, Maidah verse 64, al-Shura verse 11, and al-Ma’idah. In addition, the meaning of tawassul Surat al-Ma'idah verse 35 and al-Ahzab verse 56 was also studied. After research using descriptive analysis method with library research approach model, it was concluded that interpretation Sheikh al-'Uthaimin related to the verses of tajsim and tashbih, whether it is in the work of tafsir or non-tafsirnya. According to him, God has a face, hands, and both eyes. Then was iis what is meant by the prophet or saint, according to al-’Uthaimin this is a form of falsehood.",